Primagravida usability and user satisfaction as a digital health initiative for pregnancy educational media and remote rural monitoring - Sumunar, Dimas; Lismidiati, Wiwin; Kusumawati, Happy Indah; Lazuardi, Lutfan; Purnama, Mia (BKM Public Health and Community Medicine, 2021)
Background: Nutritional status during pregnancy is one of the critical factors to determine maternal and fetal development status, which impacts birth weight, perinatal mortality, and infant growth. The Special Region of Yogyakarta government sets a target for reducing the number of maternal and child mortality as a health priority. Monitoring pregnant women's health regularly is crucial as preventive measures and promotive approaches for mothers and fetuses. Primagravida, a web-based system, was developed to assist pregnant women in rural areas in monitoring their health, especially during the COVID-19 pandemic. This study evaluate the usability and users' satisfaction in using Primagravida. Methods: This was quantitative descriptive research with a cross-sectional design. We conducted the study in the Kalibawang Primary Health Center (PHC) service area between June - October 2021. One hundred ten pregnant women and five midwives participated in this study. Pregnant women were registered and monitored their pregnancy through a web-based service that was integrated with maternal and child health care delivered by the PHC. Pregnant women reported their health status through the Primagravida system periodically and received feedback from the PHC’s midwives. To evaluate users’ usability, the System Usability Scale (SUS), which was developed by Brooke (1996) was utilized while the researcher developed the users’ satisfaction questionnaire to measure satisfaction. Results and Discussion: Results indicated that most of the participants were satisfied with the benefits, information relevance, content adequacy and clarity, platform availability, and up-to-the-minute curated knowledge provided by the system. The utilization of this system reduced the number of visits to PHC since health monitoring could be assessed online. Regarding system usability, respondents reported a score of 70, and the average score of respondents is 66. Conclusion: Primagravida system is well adopted by pregnant women in Kalibawang District, Kulon Progo, to monitor their health and fetal status. Feature development is required to accommodate the upcoming demands in providing holistic maternal and perinatal.